The effect of processing on the extractability and molecular weight of oat beta-glucan - Anttila, Heli; Wood, Peter; Brummer, Yolanda; Sontag-Strohm, Tuula; Salovaara, Hannu (MTT, 2004)
The beneficial physiological effects of oat (1-4)(1-3)- beta-D-glucan are believed to be due to its ability to increase viscosity in the lumen of the small intestine. Viscosity is a function of the solubility and molecular weight (MW) of beta-glucan. Raw materials and processing conditions may affect the physicochemical properties of beta-glucan. The effect processing of raw materials on beta-glucan extractability and MW was studied. Oat groats that had not been heat treated, and rolled oats and bran made from heat treated oat groats were used. Beta-glucan was extracted using two methods; a physiological extraction with digestive tract enzymes at 37 EC and a hot water extraction (ca. 90EC). MW was analysed by HPSEC and extractability was analysed by flow-injection analysis using specific calcofluor binding for detection and anlaysis. The flow behaviour of the extracts was measured by steady shear measurements. The extractability of beta-glucan from oat groats that had not been heat treated was high 75% of the total present at 37 EC and 83% with hot water. Increased extraction temperature increased the amount of solubilised beta-glucan from 50% at 37EC to 72% at 90EC for the heat treated rolled oats and from 42% to 63% for the bran. The MW of beta-glucan extracted from oat groats that had not been heat treated was low (175 200) using extraction at 37 EC, but with hot water extraction MW was 1.6 million. The MW of beta-glucan from rolled oats (2.1±0.1 and 2.4±0.2 million) and from oat bran (2.7±0.2 and 2.2±0.3 million) was high and both extraction methods resulted in similar MW. Raw material processing and extraction temperature greatly affected the extractability and molecular weight of betaglucan.
Keywords: Ka; â-glucan; molecular weight; viscosity; processing